Ocular presentation of natural killer/T-cell lymphoma in a Caucasian man. (26th April 2016) - Hughes, Emily; Fogarty, Helen; Fortune, Anne; Keegan, David
Abstract : Natural killer/T-cell (NK/T-cell) lymphoma—nasal subtype, is a rare form of non-Hodgkin's lymphoma, most common in South East Asia, and can have an ophthalmological presentation. This report describes a 51-year-old Caucasian man with uveitis, recurrent retinal detachment and paraneoplastic features subsequently diagnosed as NK/T-cell lymphoma.